Pharmacological Characterization of Ruellia tuberosa Ethanolic Extract in a Rodent Model of Cognitive Impairment - Kumar, Rahul; Tyagi, Nidhi (Recent Advances in Inflammation & Allergy Drug Discovery, 2025)
<span class=
Keywords: RTEE